2016
DOI: 10.1177/2165079915607872
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Language and Culture Diversity in Occupational Safety

Abstract: Occupational health nursing plays a critical part in improving the safety of foreign labor workers. The development and implementation of safety training programs do not always regularly take into account language barriers, low literacy levels, or cultural elements. This oversight can lead to more injuries and fatalities among this group. Despite established health and safety training programs, a significant number of non-native English speakers are injured or killed in preventable, occupation-related accident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Owing to language barriers, variations in literacy levels, and unequal access to formal education, presenting safety information in English or through the use of flyers or worksheets is not adequate in multicultural work settings. Safety trainings should incorporate methods such as pictograms, illustrations, and hands-on exercises that transcend cultural, educational, and linguistic differences (22).…”
Section: Improved Safety Trainingsmentioning
confidence: 99%
“…Owing to language barriers, variations in literacy levels, and unequal access to formal education, presenting safety information in English or through the use of flyers or worksheets is not adequate in multicultural work settings. Safety trainings should incorporate methods such as pictograms, illustrations, and hands-on exercises that transcend cultural, educational, and linguistic differences (22).…”
Section: Improved Safety Trainingsmentioning
confidence: 99%
“…Groups that are more likely to have poor health literacy include individuals with lower socioeconomic status, lower educational attainment, and lower reading/writing ability; general labor workers, agricultural or rural migrant occupation workers, older adults, racial/ethnic minorities, and people with compromised health status [ 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Adequate health literacy is especially important for individuals in occupations that may involve exposure to dangerous chemicals [ 23 , 24 ]. Research has shown a link between low heath literacy and unsafe pesticide use among farmers, highlighting the importance of efforts to increase health literacy among such workers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, training should be provided in the workers' primary language if possible, particularly if it is a common language, such as Spanish. Moreover, because of the relatively low level of formal education completion, materials should be developed at a low reading level, and include pictures and symbols, instead of using text heavy formats, like books or manuals [19,33]. Trainers may consider using stories, games, role playing scenarios, verbal quizzes, peer-to-peer learning, or other types of popular education techniques, and supplementing with less engaging training methods, such as written materials, as reinforcement [14,19,34].…”
Section: Discussionmentioning
confidence: 99%